2016
DOI: 10.1002/brb3.584
|View full text |Cite
|
Sign up to set email alerts
|

Elevated cerebrospinal fluid uric acid during relapse of neuromyelitis optica spectrum disorders

Abstract: IntroductionPrevious studies have shown that serum uric acid (UA) modulates outcomes of neurological diseases, although little is known about cerebrospinal fluid (CSF) UA levels in neuromyelitis optica spectrum disorders (NMOSDs).MethodsCerebrospinal fluid and serum UA levels were measured in samples from 68 patients, including NMOSDs during relapse (n = 38) and controls with noninflammatory and non‐neurodegenerative diseases (CTLs, n = 30). Correlation analysis was performed between CSF UA and clinical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
(35 reference statements)
3
13
0
Order By: Relevance
“…In this study, the UA levels in CSF were positively correlated with serum UA, indicating that CSF UA may be partially determined by serum UA and the impaired blood-CSF or blood-nerve barrier in GBS, which is consistent with previous studies in MS and NMOSD (16,38). Female GBS patients had lower serum UA levels in the present study, but there was no gender difference in CSF, which is in line with the study of Shu et al in NMOSD (16). Lower serum UA levels in female have been identified in MS, NMOSD, and healthy controls (25,46).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, the UA levels in CSF were positively correlated with serum UA, indicating that CSF UA may be partially determined by serum UA and the impaired blood-CSF or blood-nerve barrier in GBS, which is consistent with previous studies in MS and NMOSD (16,38). Female GBS patients had lower serum UA levels in the present study, but there was no gender difference in CSF, which is in line with the study of Shu et al in NMOSD (16). Lower serum UA levels in female have been identified in MS, NMOSD, and healthy controls (25,46).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have shown inconsistent UA concentrations in neurological diseases. The UA levels in MS and other neurological diseases have been reported either increased or decreased when compared with controls in different studies (8,(12)(13)(14)(15)(16)(17). It has been reported that reduced serum UA levels are linked to the development and progression of neurological diseases, including MS, neuromyelitis optica (NMO), Alzheimer's disease, and Parkinson's disease (8,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The normal serum reference levels of uric acid are 1.5–6.0 mg/dL (89–357 μM) in women and 2.5–7.0 mg/dL (149–417 μM) in men [ 134 ], whereas the CSF urate concentration is 10- to 20-fold lower than in plasma; however, a positive correlation between plasma and CSF urate levels was reported [ 165 , 166 ]. Urate concentrations in rat CSF (6.13 ± 0.68 μM) [ 167 ] were found to be higher than in the rat brain ISF (approximately 1 μM) [ 168 ].…”
Section: Urate Transporters In Choroid Plexus Epithelial Cellsmentioning
confidence: 99%